Relationship of Individual Factors, and Social Factors with Mother’s Intention to Continue Early Marriage Tradition in Indonesia - Nurma Fuji Astutik1 , Ira Nurmala1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Early marriage is a marriage conducted by teenagers under the age of 20 who are not ready to carry out a marriage. Indonesia ranks 37th in the world and 2nd in ASEAN as a country with high rates of young marriage. Marriage at a young age affects physical, psychological and social health. The tradition of getting married at a young age is still high in Sumenep Regency. Sumenep Regency occupies the first position on the island of Madura with 2692 married women <20 years old. This happens because the tradition of young marriage still continues as a result of low individual understanding and supported by social factors. The purpose of this study was to analyze the relationship of individual factors and social factors to the mother’s intention to continue early marriage tradition in Sumenep Regency. This is a descriptive study using a qualitative approach. The method of data collection was performed qualitatively using in-depth interview and observation methods. The research instruments in this study were observation sheets and interview guidelines with a total of 32 main and key informants. Data analysis was performed using qualitative analysis including content analysis, analytical procedure, and translations. This study shows that in Sumenep, mothers with history of experiencing young age marriage had the intention to continue the tradition of early marriage. The mothers’ intention to continue the ealy marriage tradition is formed due to the existence of individual factors of past behavior and social factors including education, employment, culture, first marriage and religion. The conclusion of this study is that early marriage will continue. Therefore, cross-sector collaboration between central and regional governments, community leaders and related agencies (KUA and Health center) to reduce and prevent the occurrence of marriage of young children is required.